STUDENTS WITH POOR COMMUNICATION SKILLS IN THE DIGITAL AGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the problem of poor communication skills among students in the digital age. The rapid development of digital technologies, social media platforms, and online communication tools has significantly changed the way students interact with one another. While these technologies provide convenience and accessibility, excessive dependence on digital communication can reduce face-to-face interaction and negatively affect speaking, listening, and interpersonal skills. The article discusses the main causes of weak communication skills among students, the impact of this issue on academic and social development, and possible strategies for improvement.
Keywords: communication skills, digital age, students, social media, online communication, education, technology, interpersonal communication, speaking skills, learning